Book Reviews. Issue 1 (1st March 2016) - Block, Geoffrey; Purin, Peter; Robbins, Hannah; Stilwell, Robynn J.
On Sondheim: An Opinionated Guide, Ethan Mordden (2016) New York: Oxford University Press, 198 pp., ISBN: 9780199394814, h/bk, 27.95Music Theory Through Musical Theatre: Putting it Together, John Franceschina (2015) New York: Oxford University Press, 452 pp., ISBN: 9780199999552, p/bk, £25.99American Cinderellas on the Broadway Musical Stage: Imagining the Working Girl from 'Irene' to 'Gypsy', Maya Cantu (2015) Houndmills, Basingstoke, Hampshire and New York, NY: Palgrave Macmillan, 288 pp., ISBN: 9781137561459, h/bk, 95.00Music in the Shadows: Noir Musical Films, Sheri Chinen Biesen (2014) Baltimore: Johns Hopkins University Press, 210 pp., ISBN: 97814214-083805, p/bk, 25.00